Aspirin Exerts Its Antitumor Effect in Esophageal Squamous Cell Carcinoma by Downregulating the Expression of ATAD2 and KIF4A - Man Zhang; Zhenzhen Ren; Xianzeng Wang; Cong Liu; Zhaoyang Zheng; Junwei Zhao; Hongchun Liu (Analytical Cellular Pathology)
Objective. To investigate the expression of ATPase family AAA domain-containing protein 2 (ATAD2) and kinesin family member 4A (KIF4A) in esophageal squamous cell carcinoma (ESCC) tissues and their association with clinicopathological features and to explore the role of ATAD2 in regulating KIF4A expression and biological functions in ESCC cells and the effect of aspirin on their expression. Methods. The mRNA and protein expression of ATAD2 and KIF4A in the tissues of patients with ESCC were measured by RT-qPCR and immunohistochemistry, and the correlation between the expression of mRNA and clinicopathological characteristics was analyzed. Western blot and RT-qPCR were used to detect the interference efficiency and KIF4A expression after si-ATAD2 transfection in EC109 and KYSE30 cells. CCK-8 and Transwell assay were performed to investigate the effects of ATAD2 and aspirin on proliferation, migration, and invasion of ESCC cells. The effect of aspirin on the expression of ATAD2 and KIF4A in ESCC cells was measured by RT-qPCR and Western blot. Results. The expression of ATAD2 and KIF4A was upregulated in ESCC tissues, and both were correlated with the differentiation grades and lymph node metastasis. Knockdown of ATAD2 in ESCC cells significantly inhibited cell proliferation, migration, and invasion. Compared to the negative control group, the proliferation, migration, and invasion ability of ESCC cells in the aspirin-treated groups were decreased, and the expression of ATAD2 and KIF4A in ESCC cells was decreased after treating with aspirin for 48 h. Conclusion. The expression levels of ATAD2 and KIF4A are elevated in ESCC. ATAD2 promotes proliferation, migration, and invasion of ESCC cells by regulating KIF4A. Aspirin can inhibit the malignant behavior of ESCC cells by downregulating ATAD2 and KIF4A.